THE CONCEPT AND CHARACTERISTICS OF A CIVIL SERVANT UNDER THE IRAQI LEGISLATION - Аль-Саеді, Хайдер Саід Джихад (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2021)
Purpose: taking into account regularities, traditions and renewal of legislation, to determine attributes and formulate a concept of a civil servant in Iraq. Research methods: a basic one was represented by a comprehensive positive understanding of concepts and phenomena, which was based on the use of methods of formal-legal analysis of Administrative, Labor, Constitutional legislation, a normative retrospective of state-service conceptual characteristics; methods of analysis and synthesis that contributed to the definition of civil servant’s essential attributes and concept; a method of legal formalization was used to formulate the definition. Results: the main periods of the state service legislation development in Iraq are found and characterized; a system of normative means which promote the distinguishing and characterizing of the concept of «a civil servant» essence is defined; on the basis of the separated attributes the concept of the civil servant in Iraq is formulated. Discussion: it is suggested to reconsider the existing broad concept of the state service understanding in Iraq and based on the state approaches of leading European countries, we are representing the suggestion to introduce and use the term «public service» in Administrative Law science of Iraq. It is considered rational to distinguish between categories of employees who serve in the administrative state apparatus and perform state power functions, and employees who perform work in state enterprises, institutions, organizations without plenary powers. Emphasis is placed on the need to unify the concepts and definitions of state service and bring them into line with the provisions of the current Constitution of the Republic of Iraq.